Helminth-induced CD9+ B-cell subset alleviates obesity-associated inflammation via IL-10 production - Li, Maining; Wang, Huiquan; Ni, Yangyue; Li, Chen; Xu, Xuejun; Chang, Hao; Xu, Zhipeng; Hou, Min; Ji, Minjun (International journal for parasitology, 2022)
[Display omitted] •Schistosome infection could expand regulatory B cells (Bregs) in mice.•CD19±CD9± B cells produced more IL-10 than conventional B10 cells.•Adoptive transfer of CD9± B cells from infected mice had the capacity to markedly alleviate obesity-related inflammation.•CD9± B cells induced by helminth infection play a role in regulation of host metabolic disorders through IL-10 production. It has been shown that helminth infection can protect against obesity and improve insulin sensitivity to a certain extent, based on epidemiological investigations and animal experiments. Meanwhile, helminths induce a network of regulatory immune cells, including regulatory B cells (Bregs). However, the molecule characteristics and function of these Bregs in improving whole-body metabolic homeostasis remains largely unclear. We established a mouse model with chronic Schistosoma japonicum infection, and compared the differences in B10 cells (CD19+CD5+CD1dhi) and B10− cells (CD19+CD5−CD1d−) from splenic B cells of infected mice using RNA-seq. A unique Breg population was identified. Furthermore, these Bregs were evaluated for their ability to produce inhibitory cytokines in vitro and suppress obesity when adoptively transferred into mice on a high-fat diet. We found that schistosome infection could expand Breg cell populations in mice. CD9 was demonstrated to be a key surface marker for most murine IL-10+ B cells in spleen. CD19+CD9+ B cells produced more IL-10 than conventional B10 cells. Adoptive transfer of CD9+ B cells had the capacity to alleviate obesity-associated inflammation via promoting Tregs, Th2 cells and decreasing Th1, Th17 cells in high-fat diet mice. In conclusion, schistosome infection can induce regulatory CD9+ B cell production, which plays a critical role in the regulation of metabolic disorders through IL-10 production.